Rules for the world : international organizations in global politics - Barnett, Michael N., 1960-; Finnemore, Martha (Cornell University Press, 2004)
An innovative perspective on the behavior of international organizations and their effects on global politics. The authors argue against the conventional wisdom that these bodies are little more than instruments of state.